Perioperative changes in inflammatory biomarkers and underlying molecular mechanisms in patients with trigeminal neuralgia undergoing surgical interventions - Qiu, Cheng-Jie; Cui, Zhi-Ye; Zhang, Qi; Pan, Si-Jian; Pei, Ben-Gen (Frontiers in Neurology, 2025)
Trigeminal neuralgia (TN) is a very painful neurological condition with unilateral and electric shock-like pain attacks. The accurate diagnosis of the disease is of extreme importance for the determination of subsequent therapeutic strategies and clinical management. Surgical interventions including peripheral neurectomy, microvascular decompression (MVD), percutaneous balloon compression (PBC) and stereotaxic radiosurgery (SRS) are options for refractory patients. The utilization of proper perioperative biomarkers in serum, CSF and saliva may help in tracking the safety, efficacy and prognosis after surgical treatments. This narrative review aimed to identify potential inflammatory biomarkers that reflected perioperative changes in clinical practice and explored contributions of inflammation to pathogenesis of the disease. A total of 142 records and 95 clinical trials were identified through structured literature search and underwent subsequent selection with inclusion and exclusion criteria. We summarize relevant literature of current clinical and laboratory findings of the alterations in inflammatory biomarkers in patients with TN before and after the surgical interventions to find out biomarkers for clinical use. We then discuss the underlying molecular mechanisms based on the results from animal models for a better understanding of the role of inflammation in TN and future directions for clinical trials and basic research. Pro-inflammatory cytokines and chemokines, such as IL-1β, IL-6, TNF-ɑ reached high levels in serum, CSF or saliva specimens from TN patients, which could be reversed by PBC, but not always by MVD. The elevated preoperative level of TRAIL was reversable by MVD, but the elevated preoperative level of TNF-β was not. These alterations in inflammatory biomarkers were modulated by a variety of signaling pathways, including MAPK- or P2X7- associated pathways. Alterations in these inflammatory biomarkers could be indicative to the perioperative status of TN patients and may be used as additional outcome measurements other than pain relief in clinical trials, however, the consistency in such alterations would need to be verified in larger-scaled clinical studies.